PENGARUH PASIR CETAK DENGAN TAMBAHAN SERBUK BATU, SERBUK KAYU DAN AIR GULA TERHADAP CACAT POROSITAS DAN KEKASARAN PERMUKAAN HASIL PENGECORAN LOGAM PADUAN AL-SI - Sarip Hidayatulloh (UNIVERSITAS ISLAM MALANG, 2019)
As time goes on, the human need for metals increases. Thus encouraging small and large industrial entrepreneurs to compete to meet the needs of their consumers. casting is the process of melting metal in the smelter's kitchen, then pouring it into the mold and allowing it to freeze until it can be removed from the mold. one of the factors that can affect the quality of the results of the castings is sand mold, including the composition of the sand mold and the design of the channel system (gatting system). In this study, the aim was to analyze the variation of sand composition with addition of stone powder, wood powder, and sugar water to the porosity and roughness of metal surfaces as a result of casting Al-Si alloy metal. The material used in this study is used piston and composition of cement 5%, 6% sugar water and 4% wood powder, Banyuwangi sand composition of 60%, 55% and 50%, rock powder composition of 25%, 30% and 35% . From the results of this study, the value of porosity test results obtained from castings with the smallest value lies in the composition of sand with 50% stone powder with 35% the value of 0.26%, while the roughness test results obtained from the castings found the smallest value in the composition of sand with powder 60% stone with 25% at 1.17 μm.